2021
DOI: 10.1002/jcp.30347
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and prospects for therapeutic clinical application of noncoding RNAs in glaucoma: Systematic perspectives

Abstract: Noncoding ribonucleic acids (ncRNAs) are an increasingly studied class of RNA molecules with extensive biological activities, including important roles in human development, health, and disease. Glaucoma is a neurodegenerative disease of the retina, and one of the leading causes of blindness worldwide. However, the specific roles of ncRNAs in the development and progression of glaucoma are unclear, and related reports are fragmented. An in‐depth understanding of ncRNAs participating in the pathogenesis and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…In this study, we initially identified a few lncRNAs that may play a role in the pathogenesis of glaucoma, but did not delve into the mechanisms by which these lncRNAs are involved in the pathogenesis of glaucoma, which is an area that needs to be further explored in the future. lncRNAs are involved in the pathogenesis of glaucoma in three main ways, in addition to regulating the function of trabecular meshwork cells, participating in ECM and scar formation after glaucoma filtration surgery, and directly regulating RGC damage (37).It has been demonstrated that lncRNA may serve as a potential biomarker for primary open-angle glaucoma (38)(39)(40), and studies on the mechanism of lncRNA have mainly focused on the ceRNA mechanism. Several studies have demonstrated that lncRNA can regulate the loss of retinal ganglion cells (41-44), apoptosis of human trabecular meshwork cells and extracellular matrix deposition through the ceRNA mechanism (45-48).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we initially identified a few lncRNAs that may play a role in the pathogenesis of glaucoma, but did not delve into the mechanisms by which these lncRNAs are involved in the pathogenesis of glaucoma, which is an area that needs to be further explored in the future. lncRNAs are involved in the pathogenesis of glaucoma in three main ways, in addition to regulating the function of trabecular meshwork cells, participating in ECM and scar formation after glaucoma filtration surgery, and directly regulating RGC damage (37).It has been demonstrated that lncRNA may serve as a potential biomarker for primary open-angle glaucoma (38)(39)(40), and studies on the mechanism of lncRNA have mainly focused on the ceRNA mechanism. Several studies have demonstrated that lncRNA can regulate the loss of retinal ganglion cells (41-44), apoptosis of human trabecular meshwork cells and extracellular matrix deposition through the ceRNA mechanism (45-48).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are tissue-specific and expressed in ocular tissues related to glaucoma [ 35 ]. Several studies have highlighted the significant role of miRNAs and their plausible underlying mechanisms in different types of glaucoma, including PXG [ 8 , 36 , 37 , 38 , 39 , 40 ]. Rao et al reported the overexpression of 12 miRNAs in PXG, of which miR-122-5p, miR-124-3p, and miR-424-5p targeted TGFβ1, fibrosis/ECM, and proteoglycan metabolism pathways [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests the critical roles of microRNA (miRNA) in glaucoma [ 7 , 8 ]. miRNAs are small (~22 bp), conserved, noncoding RNAs that act by binding to complementary sequences in the 3′ untranslated region (3′ UTR) of messenger RNAs (mRNAs) to regulate posttranscriptional gene expression or translational repression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in another study using a model of H 2 O 2 -induced oxidative stress in HTM cells. Oxidative stress conditions in HTM cells significantly upregulated SNORD3A [ 39 ].…”
Section: Discussionmentioning
confidence: 99%